Experimental and theoretical studies of scanning adsorption-desorption isotherms. - Cimino, Richard; Cychosz, Katie A.; Thommes, Matthias; Neimark, Alexander V. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2013)
Scanning isotherms provide important information about the pore network geometry, including its connectivity and pore size distribution, which cannot be revealed from the main adsorption and desorption isotherms. We analyze scanning isotherms on different yet well-characterized pore structures: SBA-15 silica, KIT-6 silica, Vycor glass, and 3DOm carbons. Firstly, we suggest a partial correlation model to distinguish the importance of the pore blocking effects. Secondly, we formulate a percolation model for a quant. description of scanning desorption isotherms in the pore and neck network in two versions, the anal. Bethe approxn. and the Monte Carlo simulation on 3D cubic lattice. Thirdly, we introduce a computational method for calcg. the pore network connectivity characterized by the network coordination no. and the pore and neck size distributions. [on SciFinder(R)]
Keywords: scanning adsorption desorption isotherm theor analysis